Paradoxical Facilitation of Working Memory after Basolateral Amygdala Damage - Morgan, Barak; Terburg, David; Thornton, Helena B.; Stein, Dan J.; van Honk, Jack (PLOS ONE, 2012)
Working memory is a vital cognitive capacity without which meaningful thinking and logical reasoning would be impossible. Working memory is integrally dependent upon prefrontal cortex and it has been suggested that voluntary control of working memory, enabling sustained emotion inhibition, was the crucial step in the evolution of modern humans. Consistent with this, recent fMRI studies suggest that working memory performance depends upon the capacity of prefrontal cortex to suppress bottom-up amygdala signals during emotional arousal. However fMRI is not well-suited to definitively resolve questions of causality. Moreover, the amygdala is neither structurally or functionally homogenous and fMRI studies do not resolve which amygdala sub-regions interfere with working memory. Lesion studies on the other hand can contribute unique causal evidence on aspects of brain-behaviour phenomena fMRI cannot “see”. To address these questions we investigated working memory performance in three adult female subjects with bilateral basolateral amygdala calcification consequent to Urbach-Wiethe Disease and ten healthy controls. Amygdala lesion extent and functionality was determined by structural and functional MRI methods. Working memory performance was assessed using the Wechsler Adult Intelligence Scale-III digit span forward task. State and trait anxiety measures to control for possible emotional differences between patient and control groups were administered. Structural MRI showed bilateral selective basolateral amygdala damage in the three Urbach-Wiethe Disease subjects and fMRI confirmed intact functionality in the remaining amygdala sub-regions. The three Urbach-Wiethe Disease subjects showed significant working memory facilitation relative to controls. Control measures showed no group anxiety differences. Results are provisionally interpreted in terms of a ‘cooperation through competition’ networks model that may account for the observed paradoxical functional facilitation effect.